Creating a Historical Narrative for a Spiritual Nation: Simon Dubnow and the Politics of the Jewish Past - Gechtman, Roni (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2011)
Simon Dubnow (1860–1941) was a towering intellectual figure in the history of East European Jewry in the half-century before the Second World War. His influence was manifested mostly in two areas: as the preeminent Jewish historian of his generation and as the main theorist of Jewish diaspora nationalism (Folkism) and intellectual leader of the Folkspartey in Russia (1907-1917). This article examines the relation between the two aspects of Dubnow’s career and legacy. As a historian, Dubnow developed a method for the study of Jewish history he called ‘historism’. Politically, Dubnow was an atypical nationalist, in that he did not demand territorial independence for his people but only the recognition of Jews as a nation with autonomous status within the states where they already lived. I show how Dubnow’s Jewish nationalism and his political views derived, to a large extent, from his historical theory and analysis, and in turn, how his historical interpretations were often informed by his ideological preconceptions. By analyzing and juxtaposing his historical and theoretical works, I argue that the writing of history was for Dubnow a means to achieve his more ambitious goal: to change the future of Jewish society and, by extension, the countries where the Jews lived.